Bank Lobbying : Regulatory Capture and Beyond - Igan, Deniz (IMF Working Papers; Working Paper, 2019)
In this paper, we discuss whether and how bank lobbying can lead to regulatory capture and have real consequences through an overview of the motivations behind bank lobbying and of recent empirical evidence on the subject. Overall, the findings are consistent with regulatory capture, which lessens the support for tighter rules and enforcement. This in turn allows riskier practices and worse economic outcomes. The evidence provides insights into how the rising political power of banks in the early 2000s propelled the financial system and the economy into crisis. While these findings should not be interpreted as a call for an outright ban of lobbying, they point in the direction of a need for rethinking the framework governing interactions between regulators and banks. Enhanced transparency of regulatory decisions as well as strenghtened checks and balances within the decision-making process would go in this direction.